Regulation of Precision Farming in EU Countries - Szira Zoltán; Gregus-Greutter Éva; Greutter Zoltán; Varga Erika (EU agrarian Law)
This paper examines the regulation of precision farming in the countries of the European Union (EU), focusing on technological innovations, environmental impacts, and case studies from various member states. Precision farming, which utilizes advanced technologies to optimize agricultural practices, presents significant opportunities for enhancing productivity and sustainability. However, the integration of these technologies raises regulatory challenges that must be addressed to ensure safe and effective implementation. By analysing the regulatory frameworks and practices in different EU countries, this paper aims to identify best practices and propose recommendations for harmonizing regulations across the EU in order to support the growth of precision agriculture.